Lejeuneaceae anak suku Ptychanthoideae di Hutan Sibayak Sumatra Utara - Etti Sartina Siregar; Nunik Sri Ariyanti; Sri S. Tjitrosoedirdjo (Floribunda, 2014)
Sixteen species of Ptychanthoideae are found in Sibayak Forest North Sumatra, of which thirteen are previously known, while three are new records (Mastigolejeunea virens, Schiffneriolejeunea tumida and Thysananthus retusus) for Sumatra. An identification key to the species and description of Ptychanthoideae from Sibayak Forest, North Sumatra are provided.